Práticas docentes no SIGAA à luz dos letramentos digitais - Silva, Laila Gardênia Viana (2021)
This research, inserted in the line of research entitled Education and Communication, has as its general objective to analyze the use of the Integrated System of Management of Academic Activities (SIGAA) in teacher practices at the Federal Institute of Sergipe, São Cristóvão campus, in the light of digital literacies, to identify meanings made about the system. Embedded in the context of post-digital, this study presents theoretical discussions on society transformations, technologies and communication, then establishing a dialogue in the educational scope concerning teaching practices and digital literacies, covering the context brought by the emergence of the covid-19 pandemic. Methodologically, this research has a qualitative nature, in an analytical approach, based on a case study. Data were collected through participant observation, questionnaire, documentary analysis and semi-structured interviews. Data analysis was grounded on Freeman's (1998) teacher research perspective as well as on the coding process proposed by Auerbach and Silverstein (2003). The study revealed that the main uses of the academic system, before the pandemic context, were related to the academic record, the availability of materials, publication of information and, to a lesser extent, to the development of educational activities with students. From the first impacts caused by the pandemic, teachers carried out remote assistance through SIGAA, using chat, forum, questionnaires, didactic material and web conference. However, there was little participation by students, difficulties faced by technical disciplines and the beginning of teacher preparation for the imminence of emergency remote education. The collected data also pointed out meanings made on the system, demonstrating that teachers consider it to be a broad system, which integrates mandatory aspects, virtual repository, information, interactions, pedagogical activities and possibilities for expanding its use; the system requires improvements in its structure, functioning and teacher training; the system is seen, for most participants, as a virtual learning environment. The research shows that, although there are practices carried out with students, the uses made by SIGAA still maintain strong links to the field of technique, which reflects the lack of teacher training and the precarious infrastructure conditions.